2020
DOI: 10.1177/0890117120908505
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tailored Behavioral Weight Loss Program for Veterans With PTSD (MOVE!+UP): A Mixed-Methods Uncontrolled Iterative Pilot Study

Abstract: Purpose: Veterans with post-traumatic stress disorder (PTSD) lose less weight in the Veterans Affairs (VA) weight management program (MOVE!), so we developed MOVE!+UP. Design: Single-arm pre–post pilot to iteratively develop MOVE!+UP (2015-2018). Setting: Veterans Affairs Medical Center. Participants: Overweight Veterans with PTSD (5 cohorts of n = 5-11 [N = 44]; n = 39 received ≥1 MOVE+UP session, with cohorts 1-4 [n = 31] = “Development” and cohort 5 [n = 8] = “Final” MOVE!+UP). Intervention: MOVE!+UP weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, limited efforts have attempted to extend trauma‐informed approaches to behavioral weight‐loss interventions. A recent proof‐of‐concept study by Hoerster and colleagues (41) supported the feasibility and potential effectiveness of delivering trauma‐informed obesity care. The authors adapted an established behavioral weight‐loss program to include cognitive behavioral therapy skills relevant for trauma‐ and stressor‐related symptoms and found that these adaptations led to significant weight loss among a sample of veterans with posttraumatic stress disorder.…”
Section: Discussionmentioning
confidence: 97%
“…However, limited efforts have attempted to extend trauma‐informed approaches to behavioral weight‐loss interventions. A recent proof‐of‐concept study by Hoerster and colleagues (41) supported the feasibility and potential effectiveness of delivering trauma‐informed obesity care. The authors adapted an established behavioral weight‐loss program to include cognitive behavioral therapy skills relevant for trauma‐ and stressor‐related symptoms and found that these adaptations led to significant weight loss among a sample of veterans with posttraumatic stress disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Two other studies focused on special populations. Hoerster and colleagues [ 67 ] developed a tailored behavioral weight loss intervention for veterans with PTSD. Although not focused exclusively on sleep goals within the Veteran Affair’s MOVE behavioral weight loss program, a sleep assessment and “improvement plan” was included in one session.…”
Section: The Relationship Between Short Sleep and Weightmentioning
confidence: 99%
“…Following the 16-week program with 8 participants, 71% had clinically meaningful weight loss ( ≥ 5% of baseline weight), with an average loss of 6.1% ( SD = 2.1). PTSD and insomnia symptom severity also improved at post-treatment [ 67 ]. Another study tested a 16-week multi-component intervention (nutrition, sleep, and physical activity) vs. waitlist control among airline pilots with overweight ( N = 125; 9.6% women) [ 68 ].…”
Section: The Relationship Between Short Sleep and Weightmentioning
confidence: 99%